Voluntary Medical Male Circumcision's (VMMC) strategy for HIV prevention in Sub-Saharan Africa, prevalence, risks, costs, benefits and best practice: A scoping review study protocol of progress and unfolding insights. - Charles Maibvise; Takaedza Munangatire; Nestor Tomas; Daniel O Ashipala; Priscilla S Dlamini (PLoS ONE)
Campaigns to scale up Voluntary Medical Male Circumcision (VMMC) for the prevention of HIV transmission has been going on for years in selected Southern African countries, following recommendations from the World Health Organisations. Despite significant strides made in the initiative and its proven benefits, controversies surrounding the strategy have never ceased, and its future remains uncertain especially as some countries near their initial targets. Over the years, as the campaigns unfolded, a lot of insights have been generated in favour of continuing the VMMC campaigns, although some insights portray the impression that the strategy is not worthy of the risks and effort required, or that enough has been done, as the targets have now been achieved. This article proposes a scoping review that aims at synthesizing and consolidating that evidence into a baseline for a further systematic review aimed at developing sound recommendations for the future of the VMMC strategy for HIV prevention. The scoping review will target all scientific literature published on the Web of Science, Cochrane Library, Scopus, Science Direct, PubMed as well as grey literature from Google Scholar and WHO Institutional Repository for Information Sharing (IRIS) from the inception of the campaigns. The review shall be guided by Arksey and O'Malley's (2005) framework for scoping reviews, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) checklist shall be followed. Discussion of the findings is envisioned to yield evidence that can be further analysed to give insights about risk/cost-benefits ratios of the strategy at this point in time as well as best clinical practices for the VMMC procedure, to inform the future of the strategy. This protocol is registered with the Open Science Framework, registration ID https://doi.org/10.17605/OSF.IO/SFZC9.